Teacher skills in classroom management at MI Muhammadiyah Gonilan - Desma Dzuriansyah; Almuntaqo Zainuddin (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Teacher skills in classroom management are needed so that the learning process in the classroom can run well and follow the goals desired by teachers and students. This research was conducted to determine and describe teachers' skills in classroom management at MI Muhammadiyah Gonilan using a qualitative descriptive approach and phenomenological model. The techniques used in collecting data are observation, interviews, and documentation. This research involved two resource persons: IVa and IVb homeroom teachers. The research results, among other things, show preparation for classroom management. Before entering class, the teacher prepares lesson plans and reference books and prepares students to participate in learning. Furthermore, in building positive relationships, the teacher is in charge of creating a comfortable atmosphere. Other research results relate to the implementation of classroom management. In classroom management, some factors support the implementation process. Several supporting factors include teaching aids, teachers' accompanying books or complete teaching materials, student books, and teachers and students arriving on time. Inhibiting factors are different children's concentration and different children's comprehension abilities. AbstrakKeterampilan guru dalam pengelolaan kelas sangat dibutuhkan sehingga proses pembelajaran di kelas dapat berjalan dengan baik dan sesuai dengan tujuan yang diinginkan oleh guru dan peserta didik. Penelitian ini dilakukan untuk mengetahui dan mendeskripsikan keterampilan guru dalam pengelolaan kelas di MI Muhammadiyah Gonilan dengan menggunakan pendekatan deskriptif kualitatif dan model fenomenologi. Teknik yang digunakan dalam pengumpulan data yaitu observasi, wawancara, dan dokumentasi. Penelitian ini melibatkan dua narasumber yakni wali kelas IVa dan IVb. Hasil penelitian antara lain memperlihatkan tentang persiapan pengelolaan kelas. Sebelum memasuki kelas, guru mempersiapkan RPP, buku referensi dan menyiapkan peserta didik untuk siap mengikuti pembelajaran. Selanjutnya, dalam membangun hubungan positif, di sini guru yang bertugas menciptakan suasana nyaman. Hasil penelitian lainnya berkaitan dengan pelaksanaan pengelolaan kelas. Dalam pengelolaan kelas, terdapat faktor yang mendukung proses pelaksanaannya. Beberapa faktor pendukung seperti alat peraga, buku pendamping guru atau bahan ajar lengkap, buku peserta didik lengkap, guru dan peserta didik datang tepat waktu. Faktor penghambat adalah konsentrasi anak yang berbeda, daya tangkap anak yang berbeda-beda.Kata Kunci: Keterampilan guru; pendidikan; pengelolaan kelas.